2007
DOI: 10.1093/nar/gkl865
|View full text |Cite
|
Sign up to set email alerts
|

RegTransBase--a database of regulatory sequences and interactions in a wide range of prokaryotic genomes

Abstract: RegTransBase is a manually curated database of regulatory interactions in prokaryotes that captures the knowledge in public scientific literature using a controlled vocabulary. Although several databases describing interactions between regulatory proteins and their binding sites are already being maintained, they either focus mostly on the model organisms Escherichia coli and Bacillus subtilis or are entirely computationally derived. RegTransBase describes a large number of regulatory interactions reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 21 publications
0
89
0
Order By: Relevance
“…Functional annotations of the predicted regulon members and the associated metabolic subsystems were collected from the SEED database using recently developed Web services (9,34). Initial data about target genes and TF binding sites for several regulons previously described for S. aureus (AgrA, CzrA, GlnR, LacR, MntR, Fur, Zur, and PerR) were extracted from the RegTransBase database (http://regtransbase.lbl.gov/), a database of regulatory interactions based on data in the literature (20). The reconstructed regulons, including TFs, their target genes and operons, and associated TFBSs, were uploaded to the RegPrecise database (http://regprecise.lbl .gov/) (29).…”
Section: Methodsmentioning
confidence: 99%
“…Functional annotations of the predicted regulon members and the associated metabolic subsystems were collected from the SEED database using recently developed Web services (9,34). Initial data about target genes and TF binding sites for several regulons previously described for S. aureus (AgrA, CzrA, GlnR, LacR, MntR, Fur, Zur, and PerR) were extracted from the RegTransBase database (http://regtransbase.lbl.gov/), a database of regulatory interactions based on data in the literature (20). The reconstructed regulons, including TFs, their target genes and operons, and associated TFBSs, were uploaded to the RegPrecise database (http://regprecise.lbl .gov/) (29).…”
Section: Methodsmentioning
confidence: 99%
“…The ramp-up in microbial genome sequencing focused attention on the difficulty of accurate annotation and the need to take advantage of the information garnered for genes and proteins through painstaking biochemical and genetic research prior to the "genomics age". Therefore, an effort led by the Dubchak group (Cipriano et al, 2013;Kazakov et al, 2007) has attempted to capture the published information about gene regulation, regulon inference, transcription factors and transcription factor binding sites in a searchable format. The platform devised is RegTransBase (http://regtransbase.lbl.…”
Section: Community Resources For Comparative Genome Analysesmentioning
confidence: 99%
“…gov/cgi-bin/regtransbase?page¼main) that has two modules, a database of regulons deduced from published experimental data and a manually curated database of transcription factor-binding sites that provides the reference for determining new or conserved binding sites across species. As of November 2012, about 7200 articles back to 1977 have been curated that examined 666 bacteria (Cipriano et al, 2013;Kazakov et al, 2007).…”
Section: Community Resources For Comparative Genome Analysesmentioning
confidence: 99%
“…11). To confirm that this motif matched the AraC consensus binding sequence, we used the TOMTOM program (17) to search RegTransBase (22), a curated database of bacterial transcription factor binding sites, and found that the top hit indeed matched the AraC consensus sequence (P Ͻ 10 Ϫ16 ). We also scanned all upstream sequences in the E. coli genome using FIMO (2) and found that the only significant hits (P Ͻ 10 Ϫ10 ; q Ͻ 0.01 [41]) were the arabinose and xylose promoters.…”
Section: Vol 76 2010 Regulation Of Arabinose and Xylose Metabolism mentioning
confidence: 99%